Phytohormone profiles in non-transformed and AtCKX transgenic centaury (Centaurium erythraea Rafn) shoots and roots in response to salinity stress in vitro - Trifunović-Momčilov, Milana; Motyka, Václav; Dobrev, Petre I; Marković, Marija; Milošević, Snežana; Jevremović, Slađana; Dragićević, Ivana Č; Subotić, Angelina (Scientific reports, 2021)
Plant hormones regulate numerous developmental and physiological processes. Abiotic stresses considerably affect production and distribution of phytohormones as the stress signal triggers. The homeostasis of plant hormones is controlled by their de novo synthesis and catabolism. The aim of this work was to analyse the contents of total and individual groups of endogenous cytokinins (CKs) as well as indole-3-acetic acid (IAA) in AtCKX overexpressing centaury plants grown in vitro on graded NaCl concentrations (0, 50, 100, 150, 200 mM). The levels of endogenous stress hormones including abscisic acid (ABA), salicylic acid (SA) and jasmonic acid (JA) were also detected. The elevated contents of total CKs were found in all analysed centaury shoots. Furthermore, increased amounts of all five CK groups, as well as enhanced total CKs were revealed on graded NaCl concentrations in non-transformed and AtCKX roots. All analysed AtCKX centaury lines exhibited decreased amounts of endogenous IAA in shoots and roots. Consequently, the IAA/bioactive CK forms ratios showed a significant variation in the shoots and roots of all AtCKX lines. In shoots and roots of both non-transformed and AtCKX transgenic centaury plants, salinity was associated with an increase of ABA and JA and a decrease of SA content.
Keywords: Cytokinins; oxylipiny; cytokininy; In Vitro Techniques; Abscisic Acid; kyseliny indoloctové; kyselina salicylová; kyselina abscisová; Oxylipins; Indoleacetic Acids; regulátory růstu rostlin; Cyclopentanes; Plant Roots; techniky in vitro; Salicylic Acid; Salt Stress; kořeny rostlin; Plant Shoots; Centaurium; Plant Growth Regulators; cyklopentany; výhonky rostlin; solný stres